La realtà presuntiva del mondo: La questione della Welt nelle Idee per una fenomenologia pura - Carroccio, Andrea (B@belonline, 2020)
This article is a reading of the concept of world in Husserl’s Ideas Pertaining a Pure Phenomenology and The Crisis of the European Sciences. In these pages, we will follow the development of this concept starting from the natural attitude up to the phenomenological one. The aim of this research is to highlight the paradox of the world as a content of consciousness: on the one hand, in the natural attitude the world appears as the existing foundation of every individual consciousness; on the other, consciousness is the foundation of the world as phenomenon.